Analysis of Elevated Levels of Nandrolone Decanoate Induced Cytochrome- P450 Alterations in Mice - Chowdhury, Parmita; Mahanta, Rita (Drug Metabolism Letters, 2017)
Background: Frequent recreational use of Anabolic Androgenic Steroids (AAS) is an instance of substance abuse which mimics the status of a natural hormone and upon prolonged exposure may lead to adverse drug reactions. These adverse drug reactions proceed in a manner so as to alter the normal metabolism of an enzyme mediated pathway such as the Cytochrome P450 (CYP) family of enzymes. Objective: The present study was conducted to investigate the impact of overuse of Nandrolone Decanoate (ND), an AAS, upon CYP enzyme activity and a CYP gene, belonging to CYP1 family. Methods: The study was carried out using normal and ND treated male albino mice. Genetic analysis was conducted using normalized and treated cDNA and reverse transcriptase polymerase chain reaction based assays. For enzyme assay, 0.1ml of 25 mg ND was administered to the animals twice a week for a period of 90 days. Genetic analysis was carried out with the same dose but administered for a period of 360 days. Results: CYP enzyme activity increased significantly (p<0.01) in the ND treated group of animals compared to that in the normal group. However, no noticeable alteration was observed at the molecular level. Conclusion: From the present study it could be inferred that, at elevated doses, ND has the potential to alter hepatic CYP enzyme activity without any modification in the CYP gene. This could be due to a possible adaptive response of the living system to such drugs.
Keywords: Nandrolone Decanoate